The Urgency of Victim Impact Statements in Handling Sexual Violence Cases in Indonesia - Andries, Desebrina Lupitha; Latupeirissa, Julianus Edwin; Saimima, Judy Marria (TATOHI: Jurnal Ilmu Hukum, 2025)
Introduction: Victim Impact Statement (hereinafter referred to as VIS) is a mechanism that provides an opportunity for victims or their families to convey the psychological, physical, social, and financial impacts resulting from a criminal act. The purpose of VIS is to provide the victim’s perspective in the judicial process to help judges understand the consequences of the criminal act, especially during the sentencing phase.Purposes of the Research: The aim of this research is to examine and analyze the urgency of VIS in the Indonesian criminal justice system and its influence on sexual violence cases.Methods of the Research: This research uses a normative legal research method with a legislative approach, a conceptual approach, and a comparative approach. The data collected is analyzed qualitatively to understand the role of VIS in the criminal justice system.Findings of the Research: The results of the research show that the decision of the Padang High Court Number 119/PID.Sus/2024/PT.PDG, where the defendant was acquitted despite sufficient evidence, highlights the importance of applying VIS in the criminal justice system in Indonesia. To date, VIS has not been implemented in Indonesia, but this case reflects the need for a better mechanism to ensure that victims' rights are truly upheld in the judicial process. Therefore, integrating VIS into the Indonesian criminal justice system is necessary to enhance protection for victims, particularly in sexual violence cases.